Local Historians and the Historiography of Malay Nationalism 1945-57: The British, United Malays National Organisation (UMNO) and The Malay Left - Azmi Arifin, (Kajian Malaysia, 2014)
This article discusses the historiography of Malay nationalism based on the historical writings and interpretations of local historians. By utilising authoritative secondary sources and official British documents, this study attempts to trace the various schools of opinion on the political struggle that occurred in Malaya between 1945 and 1957. This study shows that the local historiography of Malay nationalism to date has largely focused on the history of political struggle within the United Malays National Organization (UMNO). Thus, the role played by other nationalist movements has not received proper attention in historical writings, as such movements have been considered unimportant. Several recent studies emphasise the role played by the leftist movement, but they are insufficient and tend to associate or equate leftist movements with communism. This study attempts to explain that there were other Malay nationalist movements, in addition to the right wing, leftist and communist movements, who fought for independence from the British. This article suggests that the aggressive response attributed to the many Malay political movements and the declaration of emergency in 1948 by the British were caused by threats not only from the rightist and leftist nationalists and communists, but also from religious movements that demanded the independence of Malaya and the establishment of an Islamic state. In essence, their ability to mobilise support from the Malays and non-Malays was viewed as a threat to the political survival of the British-UMNO alliance.